Additive manufacture of three dimensional metal-polymer nanocomposites through two-photon fabrication - Liu, Yaan (2020)
Two-photon fabrication is an attractive additive manufacturing (AM) technique that allows the production of 3D objects with high resolution down to 100 nm. It has been applied to fabricate nano-photonics, microelectromechanical systems (MEMS), microelectronics, microfluidic devices and biochips. In this thesis, complex 2D and 3D gold-, silver- and copper-polymer nanocomposites were additive manufactured for the first time through two-photon polymerisation (TPP) and two-photon reduction (TPR) in a single step. The research aims to investigate the printability of using simultaneous photopolymerisation and photoreduction to produce 3D metal-polymer nanocomposites that could be potentially applied to microelectronics, metamaterials and SERS (surface-enhanced Raman spectroscopy). A series of formulations were developed and prepared to assess the printability. The relationship between materials composition or processing parameter and final structures were characterised and investigated. The potential applications of fabricated structures were evaluated and discussed.